Demandable debt as a means of payment: banknotes versus checks - Charles M. Kahn; William Roberds (Federal Reserve Bank of Atlanta, 1998)
We examine the question of whether transactable forms of privately issued, demandable debt are better used as "banknotes" or "checks." The distinction between the two is that a check must be redeemed by the issuing bank with each use, whereas a banknote can circulate. We find that the answer to the question depends critically on the cost of early redemption. If this cost is small, banknotes will not circulate, so the question is moot. If this cost is large, incentive problems will prevent the issue of banknotes. For intermediate values of the early redemption cost, the option of early redemption limits the bank's risk-taking behavior, so that banknotes will be preferred over checks.
Keywords: 330; Checks; Money; Payment systems